On pairs of regular foliations in R(3) and singularities of map-germs - Martins, L. F. [UNESP]; Oliveira, R. D. S.; Tari, F. (Springer, 2008)
We study germs of pairs of codimension one regular foliations in R(3) . We show that the discriminant of the pair determines the topological type of the pair. We also consider various classifications of the singularities of the discriminant.
Keywords: foliations; 1-forms; topological equivalence; singularities